Review of Beyond Sustenance: An Exploration of Food and Drink Culture in Ireland, by Brian J. Murphy - Gabrielle Kathleen Machnik-Kekesi (Review of Irish Studies in Europe)
Review of Beyond Sustenance: An Exploration of Food and Drink Culture in Ireland, by Brian J. Murphy, Reimagining Ireland Series, Volume 119. (Oxford, Bern, Berlin, Bruxelles, New York, and Wien: Peter Lang, 2022), 308 pp., ISBN: 9781800799561, €43.30